The Impact Of Community Training By The Red Crescent On Improving First Aid Skills - Hesham Abbad Allehyani, Wadei Abdullah Badarb, Busus Ali Alzubaidi, Saleh Mohammed ali Alsuhaymi, Mohammed Mastour Alzahrani, Mohammed Musleh Almasoudi, Yahya Dahl Mahnshi, Hassan Jabir Alasmari, (Journal of International Crisis and Risk Communication Research, 2025)
Community-based first aid training programs have received rising importance in developing public health emergency preparedness and response. The International Federation of Red Cross and Red Crescent Societies (IFRC) has been a front-runner in applying mass first aid training to communities worldwide. This study takes into account the impact of Red Crescent community training programs on first aid skill development, knowledge retention, and community preparedness in an emergency. There was a mixed data analysis gathered from diversified Red Crescent courses from various countries between the years 2020-2024. Pretraining and posttraining measurement, longitudinal follow-up questionnaires, and community impact measures were conducted in the study. Red Crescent training obtained impressive first aid learning gains (average 68%), improvement in skills usage (72%), and self-confidence level gains (81%) among learners. Levels of preparedness in the community were improved by an average of 59% in the trained districts. Red Crescent community training courses effectively enhance first aid capacity and resilience within the community. Standard training technique, complemented with effective culturally modified delivery modes, yields long-term skill acquisition and knowledge acquisition.